Drivers of Customer Switching Behaviour in the Nigerian Road Transport Industry - Chukwuemeka O., Onyeagwara; I. Njelita, Chukwudi; Agu, Agu Godswill (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
The purpose of this study was to investigate the factors driving customer switching behaviour in the Nigerian road transport industry. Arguing from the theory of planned behaviour, a survey of 371 (306 valid) customers of the organized road transport industry in Nigeria’s South-East was carried out. Collected data was analyzed with multiple regression analysis (MRA) in SPSS 21.0. Findings indicate that service quality, price, and promotion are positive and significant drivers of switching behaviour, while location is not. The study recommends crafting marketing strategies around service quality, price, and promotion as effective approach to avoid customer swapping.